The colonisation of exotic species does not have to trigger faunal homogenisation : lessons from the assembly patterns of arthropods on oceanic islands - Florencio, Margarita (2015)
Human-caused disturbances can lead to the extinction of indigenous (endemic and native) species, while facilitating and increasing the colonisation of exotic species; this increase can, in turn, promote the similarity of species compositions between sites if human-disturbed sites are consistently invaded by a regionally species-poor pool of exotic species. In this study, we analysed the extent to which epigean arthropod assemblages of four islands of the Azorean archipelago are characterised by nestedness according to a habitat-altered gradient. The degree of nestedness represents the extent to which less ubiquitous species occur in subsets of sites occupied by the more widespread species, resulting in an ordered loss/gain of species across environmental or ecological gradients. A predictable loss of species across communities while maintaining others may lead to more similar communities (i.e. lower beta-diversity). In contrast, anti-nestedness occurs when different species tend to occupy distinct sites, thus characterising a replacement of species across such gradients. Our results showed that an increase in exotic species does not promote assemblage homogenisation at the habitat level. On the contrary, exotic species were revealed as habitat specialists that constitute new and well-differentiated assemblages, even increasing the species compositional heterogeneity within human-altered landscapes. Therefore, contrary to expectations, our results show that both indigenous and exotic species established idiosyncratic assemblages within habitats and islands. We suggest that both the historical extinction of indigenous species in disturbed habitats and the habitat-specialised character of some exotic invasions have contributed to the construction of current assemblages.